Concurrent opioid and alcohol withdrawal management - Michelle Colvard, PharmD, BCPP (American Association of Psychiatric Pharmacists, 2023)
Concurrent alcohol and opioid withdrawal syndrome is a common and challenging clinical scenario with little published evidence or guidance to inform pharmacotherapy strategies. Concurrent use of benzodiazepines and opioid agonists, which are considered first-line agents for management of each withdrawal syndrome independently, is controversial and often avoided in clinical practice. Strategies to provide effective, simultaneous medication treatment of alcohol and opioid withdrawal while optimizing patient safety are demonstrated through 3 patient cases.